Carry on, warrior : the power of embracing your messy, beautiful life - Doyle, Glennon, 1976- (Scribner, 2014)
You don't have to be strong. Through humor and her own real-life stories, Melton encourages readers to forget about the tough exterior stuff and throw away the armor and acknowledge that life is hard. This, Melton says, is the key to living a better life and making lasting differences.